Pengaruh Self-Efficacy dan Dukungan Orang Tua terhadap Semangat Menghafal Al-Qur'an Santri di Tahfiz Al-Qur'an Arrahim, Kabupaten Kerinci, Provinsi Jambi - Radia Aflani; Edy Kusnadi (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
The Qur'an is the holy book of Islam and serves as the fundamental foundation and primary guide for Muslims in their daily lives.This study aims to determine the influence of self-efficacy and parental support on the enthusiasm for memorizing the Qur'an among students at Tahfiz Al-Qur'an Arrahim, Kerinci Regency, Jambi Province. The population of this study consisted of students of Tahfiz Al-Qur'an Arrahim, with a sample of 55 students. The data collection methods used in this research were observation and questionnaires with quantitative metodhods. The results of the study indicate that self-efficacy has a positive influence on students' enthusiasm for memorizing the Qur'an at Tahfiz Al-Qur'an Arrahim, Kerinci Regency, Jambi Province, as indicated by T count < T table (0.252 < 2.00404). Furthermore, parental support has a negative influence on students' enthusiasm for memorizing the Qur'an at Tahfiz Al-Qur'an Arrahim, Kerinci Regency, Jambi Province, as indicated by T count < T table (0.300 < 2.00404).